Dynamic Network Notation: A Graphical Modeling Language to Support the Visualization and Management of Network Effects in Service Platforms - Scholten, Ulrich (KIT Scientific Publishing, 2013)
Service platforms have moved into the center of interest in both academic research and the IT industry due to their economic and technical impact. These multitenant platforms provide own or third party software as metered, on-demand services. Corresponding service offers exhibit network effects. The present work introduces a graphical modeling language to support service platform design with focus on the exploitation of these network effects.